2005
DOI: 10.1111/j.1432-2277.2004.00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of hepatic artery configuration in 3D CT angiography compared with conventional angiography - special reference to living-related liver transplant donors

Abstract: Summary Although an accurate anatomical understanding of the hepatic arteries is the most and essential step in living‐related liver transplantation (LRLT), the need to reduce the burden place on the donor should be considered in imaging diagnosis. The present study examined the reliability of intravenously enhanced three‐dimensional (3D) angiography from multidetector‐row computed tomography (MDCT) in evaluating the anatomical configuration of the hepatic arteries comparing with those from conventional angiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Reliability of the 3D MD-CT on the anatomical evaluation of the living liver donors has been reported in several articles [12,13,[20][21][22][23]. The advantages of MD-CT are mainly faster scanning capability, improved temporal resolution, improved spatial resolution and increased effectiveness of the intravascular contrast agent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reliability of the 3D MD-CT on the anatomical evaluation of the living liver donors has been reported in several articles [12,13,[20][21][22][23]. The advantages of MD-CT are mainly faster scanning capability, improved temporal resolution, improved spatial resolution and increased effectiveness of the intravascular contrast agent.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of MD-CT are mainly faster scanning capability, improved temporal resolution, improved spatial resolution and increased effectiveness of the intravascular contrast agent. Sakai et al [12] reported that, comparing with conventional angiography, 3D CT angiography depicted the extra hepatic arteries and the aberrant arteries successfully and also depicted the intrahepatic segmental arteries with a high detection rate. These results are comparable with the other published literature [13,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-detector row CT may not be a perfect reference standard for this purpose. However, in a growing body of studies, multi-detector row CT, with its high spatial resolution, is being recommended as a noninvasive imaging modality for hepatic vasculature mapping (12,(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of MD-CT are mainly faster capability, improved temporal resolusion, improved spatial resolusion and increased effectiveness of the intravascular contrast agent. Reliability of the 3D MD-CT on the anatomical evaluation has been reported in several articles 5,6,9,10) . However, a problem is that 3D reconstruction imaging does not protect www.intechopen.com …”
Section: Diagnostic Examinationmentioning
confidence: 99%